2018
DOI: 10.4103/ijccm.ijccm_101_18
|View full text |Cite
|
Sign up to set email alerts
|

What happens to patients discharged against medical advice?

Abstract: Introduction:Discharge against medical advice (DAMA) when requested by family members of patients in Indian Critical Care Units (CCUs) leads to loss of follow-up and unknown patient outcomes. Exclusion of these patients from research analysis and quality audits confounds these results. We hence explored the proportion of patients leaving DAMA, reasons, and their outcomes at 30 and 90 days.Methods:This was a prospective study of CCU patients admitted from July 2013 to February 2014. All patients, who were DAMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Two patients registered in this study received treatment and were later not permitted to leave the hospital premises until they settled their debts. This situation likely caused psychological distress and negatively impacted their recovery, as suggested in the literature [ 42 , 43 , 44 ]. Findings from this study revealed that survivors of DAMA cases were more likely to have disabilities and a poorer quality of life six months after injury than survivors discharged regularly ( p = 0.019 for QoLIBRI).…”
Section: Discussionmentioning
confidence: 99%
“…Two patients registered in this study received treatment and were later not permitted to leave the hospital premises until they settled their debts. This situation likely caused psychological distress and negatively impacted their recovery, as suggested in the literature [ 42 , 43 , 44 ]. Findings from this study revealed that survivors of DAMA cases were more likely to have disabilities and a poorer quality of life six months after injury than survivors discharged regularly ( p = 0.019 for QoLIBRI).…”
Section: Discussionmentioning
confidence: 99%
“…However, only 9% of their patients were discharged because of an overall poor prognosis. 9 Thus classifying all TDs does overestimate mortality, but excluding them would grossly underestimate mortality.…”
Section: Discussionmentioning
confidence: 99%
“…For the primary analysis, patients who left the ICU against medical advice (LAMA) were considered to have been discharged alive. Because these patients may be more likely to die [ 26 ], we conducted a best-worst and worst-best sensitivity analysis. The best-worst analysis considered non-frail patients with LAMA status to be alive, while frail patients were considered dead.…”
Section: Methodsmentioning
confidence: 99%